Improvement in oxidation resistance of Ti2AlNb alloys at high temperatures by laser shock peening. (15th May 2021) - He, Dongsheng; Li, Liuhe; Guo, Wei; He, Guangzhi; Peng, Peng; Shao, Tianwei; Huan, Heng; Zhang, Gongxuan; Han, Guofeng; Yan, Jianfeng
Highlights: The effects of the LSP on the oxidation resistances of Ti2 AlNb-based alloys were investigated at high temperatures (720 °C). Finer grains and higher density dislocations appeared to be key factors for the formation of Al-rich oxidation layers. The improvement in oxidization resistance was attributed to the higher nucleation and oxidation rates of the Al2 O3 layers. Abstract: Ti2 AlNb-based alloys exhibit attractive properties and it is challenging to increase their environmental stability at high temperatures. Laser shock peening (LSP) was employed to improve their oxidation resistances at high temperatures. After LSP, high-density dislocations and finer grains were generated, and increases in microhardness and compressive residual stress were observed. During isothermal oxidation tests at 720 °C, mass gains evidently decreased, with finer oxidation particles and a thinner oxidation layer observed in the impacted samples. Microstructural changes facilitated the formation of Al-rich oxidation layers, which stands for the main reason behind the improvement in high-temperature oxidation resistance of Ti2 AlNb-based alloys.